2009
DOI: 10.1128/jb.01131-08
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Coupling between the Lid and Interdomain Linker in DnaK Revealed by Inhibitor Binding Studies

Abstract: The molecular chaperone DnaK assists protein folding and refolding, translocation across membranes, and regulation of the heat shock response. In Escherichia coli, the protein is a target for insect-derived antimicrobial peptides, pyrrhocoricins. We present here the X-ray crystallographic analysis of the E. coli DnaK substratebinding domain in complex with pyrrhocoricin-derived peptide inhibitors. The structures show that pyrrhocoricins act as site-specific, dual-mode (competitive and allosteric) inhibitors, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 55 publications
2
44
0
2
Order By: Relevance
“…Docking of the atomic structures of an antibody molecule 30 and Hsp70 SBD (ref. 31) into their corresponding masses reinforced the location of the latter. This result was confirmed by an independent experiment using the Fab (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Docking of the atomic structures of an antibody molecule 30 and Hsp70 SBD (ref. 31) into their corresponding masses reinforced the location of the latter. This result was confirmed by an independent experiment using the Fab (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…As PrAMPs bind to DnaK with only a 7-to 8-residue-long sequence stretch (9,17,20), whereas both termini protrude out of the PrAMP-DnaK complex, an influence of the penetratin sequence on the inhibition of DnaK appears unlikely. Furthermore, the intracellular distributions of PrAMPs and penetratin-PrAMP conjugates appeared to be identical.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several laboratories have started to optimize PrAMPs for clinical applications, e.g., A3-APO (25), Bac7 (12), oncocin (16), and Api88 (9), which proved successful in rodent infection models (1,15,32). Mechanistically, PrAMPs and the related designer peptides enter the bacteria and kill them, most likely by inhibiting the 70-kDa bacterial chaperone DnaK (17,20,24). The low toxicity toward mammalian cell lines is attributed to the fact that short PrAMPs appear to enter only some cells of the immune system, without inhibiting their intracellular chaperones, but are excluded from other mammalian cells (18,26,33).…”
mentioning
confidence: 99%
“…The MIC values of these Api137 analogs indicated that the N-terminal sequence tolerated substitutions without major effects on the antibacterial activity (Fig. 4A), although apidaecins and Api88 are presumed to inhibit DnaK by binding of residues 3 to 11 to the substrate binding domain of DnaK (19,35,36). Substitutions of C-terminal residues (Pro-11 to Leu-18) significantly reduced the antibacterial activity in most cases.…”
Section: Fig 1 Degradation Of Api88 In 25% Aqueous Mouse Serum (Top) mentioning
confidence: 99%